Membangun Kemampuan Berfikir Kritis Peserta Didik Dalam Pembelajaran IPA SMP Melalui Lesson Study Berbasis MGMP - Amali Putra; Yurnetti Yurnetti; Rizanur Hasnina (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract – In order to build students' critical thinking skills through increasing the professionalism of teachers gathered in Payakumbuh MGMP IPA, activities in the form of Community Partnership Programs have been carried out with training and practice of Lesson Study activities from 7 September to 12 October 2019 with 3 activities, namely: The essence of critical thinking capability socialization, training in the application of science learning with scientific approaches, and the socialization and implementation of lesson study activities. Based on obtained data during and at the end of the activity concluded that by training the application of a scientific approach through the activity of lesson study was able to build a learning community of teachers in the MGMP IPA Middle School, in Payakumbuh which is indicated by the increasing quality of teacher perceptions of science learning, scientific approach and lesson study. The observations also showed a change in the ability to think critically and student learning outcomes for the betterKeywords : learning science, scientific approach, critical thinking skills, lesson study